Civil War & the Current International System - Fearon, James D. (Daedalus, 2017)
This essay sketches an explanation for the global spread of civil war up to the early 1990s and the partial recession since then, arguing that some of the decline is likely due to policy responses by major powers working principally through the United Nations. Unfortunately, the spread of civil war and state collapse to the Middle East and North Africa region in the last fifteen years has posed one set of problems that the current policy repertoire cannot address well–for several reasons, conflicts in this region are resistant to “treatment” by international peacekeeping operations–and has highlighted a second, deeper problem whose effects are gradually worsening and for which there does not appear to be any good solution within the constraints of the present UN system. That is, for many civil war–torn or “postconflict” countries, third parties do not know how to help locals build a self-governing, self-financing state within UN-recognized borders or, in some cases, any borders.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE2Mi9kYWVkX2FfMDA0NTY